Empirical assessment of pension fund assets on Malaysian economic growth - Said Ali Batu Shah, Syed Shaniff; Zahid, Putra Faizurrahman; Baharudin, Mohamad Hanif (International Journal of Accounting, Finance and Business, 2025)
This study examines the contribution of pension fund assets to economic growth in Malaysia, with a diversified pension system encompassing both defined benefit and defined contribution schemes. Focusing on Malaysia’s three principal pension institutions, which are the Civil Service Pension Scheme (KWAP), the Employees Provident Fund (KWSP), and the Armed Forces Pension Board (LTAT). These schemes collectively account for the vast majority of retirement savings in Malaysia and represent distinct segments of the labour force, namely the public sector, private sector, and armed forces, which is the centred novelty of this study. Using macroeconomic and combined pension funds data, the analysis evaluates the extent to which the accumulation and allocation of pension assets contribute to Malaysia’s economic growth. Overall, the results highlight that capital formation, public debt, and interest rate movements play significant roles in explaining Malaysia’s economic growth. At the same time, institutional fund activities (RETF) and domestic credit expansion (DCPS) exhibit negative associations that warrant further policy consideration. The model demonstrates acceptable statistical validity and provides a sound empirical basis for subsequent policy and strategic interpretation.